Chemical Characteristics of Catfish (Pangasius pangasius) Processing Liquid Waste - Apri Mujiyanti; Nirmala Efri Hasibuan; Putri Wening Ratrinia; Aulia Azka; Sumartini Sumartini; Muh Suryono; Basri Basri; Kurnia Sada Harahap; Shiffa Febyarandika Shalichaty (Fakultas Perikanan dan Kelautan, Universitas Riau, 2023)
Catfish is the main commodity fish smoking in the Kampar area. Increasing the amount of production causes the waste obtained to be higher. If waste is not managed properly it will pollute the environment. Liquid organic fertilizer is an alternative utilization of processing waste. The purpose of this study was to determine the characteristics of the elements N, P, and K in liquid organic fertilizer from catfish processing wastewater. Making liquid fertilizer is done through fermentation techniques. In this case the fermentation was carried out with variations in the time range, 10, 15 and 20 days with variations in the addition of the volume of EM4 microorganisms 0 ml, 10 ml, 20 ml and 30 ml. The catfish waste liquid fertilizer is dark brown to brownish yellow with a pH ranging from 6.65 -7.03. The highest N, P, and K content of catfish waste liquid fertilizer was found to be nitrogen (N) 0.55% with the addition of EM4 30ml with a fermentation time of 10 days, phosphorus (P) 1.01% without the addition of EM4 with a fermentation time of 20 days, and potassium (K) 0.32% with the addition of EM4 30 ml with a fermentation time of 15 days.